Characterization of the impact of nanoparticles on micro strain in 2D graphene synthesized by arc discharge plasma. (December 2020) - Roslan, M.S.; Haider, Z.; Chaudhary, K.T.
Graphical abstract: Highlights: High crystalline graphene layers were deposited by arc discharge plasma. The impact of nanomaterial induces defects and micro strain on graphene layer. Number of graphene layers can be tuned by background pressure arc plasma. Abstract: In this study, we report the impact of side growth of nanoparticles on crystalline graphene nanostructure by facile and stable arc discharge plasma method. The plasma generated between two highly purity graphite electrodes, not only exfoliate graphene layers on cathode surface, but also produces micro and nanoparticles. The characterization of microstructures produced on the graphene layers deposited under different background environments and pressures by arc discharge plasma is presented. The morphologies of graphene sheets, comprising eight to twelve layers, were confirmed using transmission electron microscopy (TEM). Furthermore, the increment of background pressure from 10 −2 to 10 2 mbar has found to increase numbers of graphene layers resulting in a reduction in I2D /IG ratio. Tuning the background environment and pressure led to different levels of carbon nanoclusters embedment on the surface of graphene layer under the air and H2 environments. This embedment demonstrates the rise of microstrain in the form of tensile stress on graphene indicated by Williamson-Hall plot calculated at 1232 × 10 −3 and 151 × 10 −3 respectively under H2 and air. The redshift and splitting of G and 2D bands in Raman spectra also support the rise of strain in graphene layers. Overall, embedment of nanoparticles might be accounted by the increase in stress on graphene layers that manipulate the electronic interaction between layers, suggesting it a promising candidate for nanoelectronic and nanophotonic device applications based on graphene.